2007
DOI: 10.1677/erc-06-0026
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide, a multiple somatostatin receptor subtypes ligand, reduces cell viability in non-functioning pituitary adenomas by inhibiting vascular endothelial growth factor secretion

Abstract: Somatostatin (SRIF) analogs have been employed in medical therapy of non-functioning pituitary adenomas (NFA), with contrasting results. Previous evidence showed that SRIF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 36 publications
9
53
0
2
Order By: Relevance
“…Pasireotide also inhibits IGF-1 action and induces apoptosis in mammary gland through a non-pituitary mechanism in intact and hypophysectomized female rats (Ruan et al, 2006). In additition, Pasireotide inhibits VEGF secretion and cell viability in human non-functioning pituitary adenomas primary cultures, and suppresses cell proliferation and ACTH secretion in primary cultures of human corticotroph tumors (Batista et al, 2006;Zatelli et al, 2007). These results support the hypothesis that pasireotide may have potential in the treatment of these tumors.…”
Section: Novel Somatostatin Analogs With Anti-tumor Capacitysupporting
confidence: 60%
See 1 more Smart Citation
“…Pasireotide also inhibits IGF-1 action and induces apoptosis in mammary gland through a non-pituitary mechanism in intact and hypophysectomized female rats (Ruan et al, 2006). In additition, Pasireotide inhibits VEGF secretion and cell viability in human non-functioning pituitary adenomas primary cultures, and suppresses cell proliferation and ACTH secretion in primary cultures of human corticotroph tumors (Batista et al, 2006;Zatelli et al, 2007). These results support the hypothesis that pasireotide may have potential in the treatment of these tumors.…”
Section: Novel Somatostatin Analogs With Anti-tumor Capacitysupporting
confidence: 60%
“…These growth factors are secreted by tumor cells as well as by stroma cells and stimulate endothelial and smooth muscle cell proliferation and migration, which are important processes in angiogenesis. In various human cellular models such as glioma cell lines, retinal pigment epithelial cells or non-functioning pituitary adenoma, somatostatin or analogs inhibit VEGF synthesis at the protein and mRNA levels (Mentlein et al, 2001;Sall et al, 2004;Zatelli et al, 2007). Octreotide inhibits tumor expression of VEGF as well as VEGF serum level in colorectal cancer patients (Cascinu et al, 2001).…”
Section: Indirect Antitumor Effects Of Somatostatinmentioning
confidence: 99%
“…Among the currently available SSAs, pasireotide represents the most promising compound, given its 11-fold higher functional activity on SSTR3 than octreotide and lanreotide. Evidence obtained during in vitro studies that pasireotide inhibits the viability of NFPAs in primary cultures (Zatelli et al 2007) further supports the hypothesis that SSTR3 is a suitable target for treatment. Indeed, the anti-proliferative effect of pasireotide on NFPAs cultures, in addition to a suppressive action on VEGF secretion (Zatelli et al 2007), may also be mediated by pathways downstream of SSTR3.…”
Section: Discussionmentioning
confidence: 76%
“…These studies have shown that SSTR2-aimed SSAs are usually ineffective (Kopczak et al 2014, Peverelli et al 2015, although there is high expression of SSTR3 and SSTR2 and lower expression of SSTR5 (Taboada et al 2007, Zatelli et al 2007, Florio et al 2008, Tateno et al 2009, Hofland et al 2010, Lee et al 2015, Ibáñez-Costa et al 2016). An in vitro study which used individual and combined SSTR 235:3 agonists suggested that SSTR1 agonists might be useful (Zatelli et al 2004), and moreover, that pasireotide may reduce cell viability in vitro via the inhibition of VEGF (Zatelli et al 2007). Indeed, the use of pasireotide was proposed for non-functioning pituitary adenoma patients (Colao et al 2008), as it has been reflected in two clinical trials (NCT01620138 and NCT01283542; https://clinicaltrials.gov).…”
Section: Somatostatin Analogues and Pituitary Adenomasmentioning
confidence: 99%